SHEEP BUSINESS MANAGEMENT IN BUMDES DESA CIBADAK KECAMATAN BANJARSARI CIAMIS JAWA BARAT DISTRICT - Latifah Adnani; Trisa Nur Kania (JEES: Journal of Economic Empowerment Strategy, 2020)
After the promulgation of Local Government Law number 32 of 2004 which was updated with Law Number 23 of 2014 concerning Regional Government, and strengthened by the enactment of village law number 6 of 2014 which states that to further improve the welfare of rural communities, one of the efforts that can be done is by establishing a Village-Owned Enterprises (BUMDes). The purpose of the BUMDes can be among other things to stimulate the development of rural economy, also to minimize urbanization of rural residents, the existence of independence in the village economic sector, so as to increase the original income of the village. Research that is done using qualitative research design research that is research that focuses on certain phenomena that do not have generalizability and comparability but have internal validity and contextual understanding.The conclusions of the research on managing sheep business are: As an effort to look for opportunities in determining market position, the BUMDes Cibadak makes sheep sheds that are clean, attractive, made from teak waste material, form a cage like a series of villages so that they are expected to attract consumers. The impact of sheep business management by BUMDes Cibadak for the community, is the community feels they have the existence of these business activities because most of the community are farmers including farmers as well so that they are familiar with the business of raising livestock including sheep.